Preferences of people with type 2 diabetes for telemedical lifestyle programmes in Germany: protocol of a discrete choice experiment - Veronika Gontscharuk; Andrea Icks; Michael Roden; Markus Vomhof; Sandra Grobosch; Jana Sommer; Jan Dyczmons (BMJ Open)
Introduction Telemedical lifestyle programmes for people with type 2 diabetes mellitus (T2DM) provide an opportunity to develop a healthier lifestyle and consequently to improve health outcomes. When implementing new programmes into standard care, considering patients’ preferences may increase the success of the participants. This study aims to examine the preferences of people with T2DM with respect to telemedical lifestyle programmes, to analyse whether these preferences predict programme success and to explore the changes that may occur during a telemedical lifestyle intervention.Methods and analysis We outline the protocol of the development and assessment of a discrete choice experiment (DCE) to examine patient preferences in a telemedical lifestyle programme with regard to the functions of the online portal, communication, responsibilities, group activities and time requirements. To develop the design of the DCE, we conducted pilot work involving healthcare experts and in particular people with T2DM using cognitive pretesting. The final DCE is being implemented within a randomised controlled trial for investigating whether participation in a telemedical lifestyle intervention programme sustainably improves the HbA1c values in 850 members of a large German statutory health insurance with T2DM. Preferences are being assessed before and after participants complete the programme. The DCE data will be analysed using regression and latent class analyses.Ethics and dissemination The DCE study has been approved by the ethics committee of the medical faculty of the Heinrich Heine University Duesseldorf, registration number 2018-242-ProspDEuA, registered on 6 December 2018. The TeLIPro trial is registered at the US National Library of Medicine, registration number NCT03675919, registered on 15 September 2018. We aim to disseminate our results in peer-reviewed journals, at national and international conferences and among interested patient groups and the public.